
zip [1,2,3] [4,5,6] = zip (1:2:3:[]) (4:5:6:[]) = foldr f e (1:2:3:[]) (4:5:6:[]) = f 1 (foldr f e (2:3:[])) (4:5:6:[]) = (1, 4) : foldr f e (2:3:[]) (5:6:[]) = (1, 4) : f 2 (foldr f e (3:[])) (5:6:[]) = (1, 4) : (2, 5) : foldr f e (3:[]) (6:[]) = (1, 4) : (2, 5) : f 3 (foldr f e []) (6:[]) = (1, 4) : (2, 5) : (3, 6) : foldr f e [] [] = (1, 4) : (2, 5) : (3, 6) : e [] = (1, 4) : (2, 5) : (3, 6) : [] = [(1, 4), (2, 5), (3, 6)] On 12 Mar 2009, at 20:01, R J wrote:
Can someone provide a complete hand calculation of zip [1,2,3] [4,5,6] using the following definition of zip, based on foldr:
zip :: [a] -> [b] -> [(a, b)] zip = foldr f e where e ys = [] f x g [ ] = [] f x g (y : ys) = (x , y) : g ys
foldr :: (a -> b -> b) -> b -> ([a] -> b) foldr _ e [] = e foldr f e (x : xs) = f x (foldr f e xs)
This implementation of zip produces the expected result [(1, 4), (2, 5), (3, 6)], but I'm unable to do the hand calculation and don't understand why it works. Part of my problem is that "e" is defined as a function that takes one argument, I don't see how that fits in with the usual scheme for foldr, which, as I understand it, is:
foldr f e [x1, x2, ...] = f x1 (f x2 (f x3 ...(f xn e)))...
Thanks, as always, to all in this great community.
Windows Liveā¢: Keep your life in sync. Check it out._______________________________________________ Haskell-Cafe mailing list Haskell-Cafe@haskell.org http://www.haskell.org/mailman/listinfo/haskell-cafe